Influence of minimalist footwear on knee and ankle loads during the squash lunge - Sinclair, J.; Bottoms, L.; Taylor, P. J.; Mahmood, K. (Movement & Sport Sciences - Science & Motricité, 2016)
Squash is associated with a high incidence of knee and ankle joint injuries. The aim of this work was to examine the effects of squash specific, running shoes and minimalist footwear on knee and ankle loads during the lunge movement in squash players. Twelve male squash players performed lunge movements whilst wearing squash specific, running shoes and minimalist footwear. The loads experienced by the knee and ankle joints were calculated. Patellofemoral forces were significantly greater in running shoes (5.10 B.W) compared to minimalist footwear (4.29 B.W). Achille tendon forces were significantly larger in the minimalist footwear (3.10 B.W) compared to the running shoes (2.64 B.W) and squash specific footwear (2.88 B.W). This shows that whilst minimalist footwear may reduce the incidence of knee pathologies in squash players corresponding increases in ankle loading may induce an injury risk at this joint.